ROLE IN MONITORING COMMITTEE IMPROVING COMPLIANCE WITH TAX PAYERS AND EFFECT ON REVENUE TAX INCREASE PERSPECTIVE ON ADMINISTRATION - Masyhur, Hadi (Universitas Pendidikan Indonesia, 2012)
Applicable taxes in Indonesia can be differentiated taxation based on the parties to bear, the party picked up, and nature. Good service will encourage taxpayer compliance to implement taxation obligations. To be able to improve taxpayer compliance is by listening, seeking out and trying to meet what is desired by the taxpayer regardingthe rights and obligations of taxation. The desire or the means to listen to the voice of taxpayers in many countriesknown as the Tax Ombudsman in Indonesia called the Supervisory Committee of Taxation (KPPer). Giving you the best possible service to taxpayers will increase the level of taxpayer compliance. The high level of taxpayer compliance by itself will increase tax revenues. KPPer is to ensure that the taxpayer has be best served by the DGT,namely: (1) ensure that the taxpayer has been given the ministry (in terms of policy, legal, and administrative), (2)Directorate General of Taxation to give optimal service, (3) KPer and DGT synergistically provide optimum servicesand in turn increase tax revenue will be achieved. In other words, the formation of synergies between the DGT andKPPer can increase tax revenues.